2020
DOI: 10.1093/ehjci/jeaa311
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial mechanics for secondary prevention from embolic stroke of undetermined source

Abstract: Aims  Anticoagulation is not justified unless atrial fibrillation (AF) is detected in cryptogenic stroke (CS) patients. We sought to explore whether left atrial (LA) remodelling is associated with embolic stroke of undetermined source (ESUS). Methods and results  In this prospective study, we evaluated consecutively 186 patients in sinus rhythm who presented with an acute ischaemic stroke (embolic and non-embolic) and sex- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
0
42
1
Order By: Relevance
“…One study [24] revealed statistically decreased GLS in patients with AF occurrence compared to patients without. But the other four studies [19,20,22,23] indicated there was no difference in GLS. As meta-analysis, the pooled analysis showed a significant decrease in GLS measured at the period of cryptogenic stroke in patients with AF occurrence compared to patients without AF occurrence.…”
Section: Difference In Gls Between Patients With and Without Occurrence Of Afmentioning
confidence: 96%
See 1 more Smart Citation
“…One study [24] revealed statistically decreased GLS in patients with AF occurrence compared to patients without. But the other four studies [19,20,22,23] indicated there was no difference in GLS. As meta-analysis, the pooled analysis showed a significant decrease in GLS measured at the period of cryptogenic stroke in patients with AF occurrence compared to patients without AF occurrence.…”
Section: Difference In Gls Between Patients With and Without Occurrence Of Afmentioning
confidence: 96%
“…The flow diagram of the search strategy of studies was shown in Figure 1. A total of 718 potentially relevant citations were retrieved from PubMed, Embase and the Cochrane Library, of which eight studies containing 1483 patients met the inclusion criteria and were therefore included [1,[18][19][20][21][22][23][24]. Among these studies, five, seven, four, six studies investigated the differences in GLS, εR, εCD, εCT, respectively, between patients with and without occurrence of AF following cryptogenic stroke; And three studies investigated the differences in SRs, SRe or SRa, between patients with and without occurrence of AF following cryptogenic stroke.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Abnormal LAS is a proven predictor of AF occurrence, especially in patients after cryptogenic stroke [38,39]. Recently, Kawakami et al proposed an innovative approach, analyzing whether the assessment of LA strain brings additional benefits against well-established LV strain analysis.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…The baseline LA strain was the most useful parameter in the prediction of AF recurrence, with a 0.84 area under the curve. Finally, LA strain has recently been shown to identify patients at high risk of AF among those that suffered from cryptogenic stroke, suggesting that echocardiographic quantification of LA remodeling has the potential for secondary prevention in this population [ 64 ].…”
Section: Evaluation Of Fibrosis For Prognosis and Imaging To Guide Ablationsmentioning
confidence: 99%